Varieties of religious invention founders and their functions in history - Gray, Patrick 1970- (Oxford University Press, 2016)
What does it mean to call someone the "founder" of a religion? How have debates about figures such as Jesus, Muhammad, and Confucius served as proxies for broader cultural, theological, or political questions?